Residual Gas Noise in the Test-mass Module for DECIGO Pathfinder. (April 2015) - Okutomi, K; Akutsu, T; Ando, M; Nikaido, M; Tanaka, N; Torii, Y; Sato, S; Izumi, K; Chen, D; ,
Abstract: DECIGO Pathfinder is the first milestone mission for DECIGO, a future gravitational wave antenna. In DPF, residual gas noise acting on the test mass is estimated to increase and exceed the requirement for force noise of 1 × 10 -15 N/√Hz due to geometry of the test-mass module. We performed a Monte Carlo simulation to calculate the residual gas noise and found that the engineering model of the test-mass module cannnot satisfy the requirement. To reduce the gas noise, we present revised geometry of the test-mass module using comb-like electrodes.